PENGARUH BEBAN KERJA DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. NUANSA METTA ABADI (NMA) KABUPATEN PURWAKARTA - Nabila, Syifa; Prabowo, R.M. Juddy (Politeknik Negeri Ambon, 2025)
Introduction: PT. As a construction company, Nuansa Metta Abadi (NMA) has a big responsibility to ensure its production employees' performance stays on point. However, according to internal company data, most employees don't meet the standards. This is probably because of high workloads and financial compensation that employees don't feel is fair or reasonable. This study aims to analyse how workload and monetary compensation, both individually and in combination, impact the job performance of production staff at PT. Nuansa Metta Abadi.Methods: The data for this study were collected through questionnaires and records, making it a quantitative study. Forty-two individuals working in the production department participated in the survey. The analytical process employed quantitative descriptive and correlational approaches, complemented by multiple linear regression and determination coefficient techniques to evaluate the data.Results: The study demonstrates that each variable—workload and financial compensation—positively contributes to employee performance when assessed in isolation. Simultaneously, both variables also significantly influence the performance of production employees.Conclusion and suggestion: PT. Nuansa Metta Abadi is advised to improve work environment comfort, ensure timely compensation, and enforce punctual task completion. These efforts support stronger motivation and performance. Future research should examine broader variables and larger samples to deepen understanding and broaden the study's theoretical scope. Keywords: Workload, Financial Compensation, Employee Performance, Production, Construction.